PERENCANAAN STRUKTUR BANGUNAN HOTEL ENAM LANTAI - Sri Martini, RA; Setiawati, Mira; Nauvaliyanto, Fathur (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2019)
Multi-storey buildings are vertical buildings that are made to meet human needs as places of education, government, commerce, sports facilities and others. As the development of science and technology, especially in the field of civil engineering, many computer programs have been developed to help in analyzing and designing a building structure. There are several computer programs developed to analyze and design structures, including SAP 2000 (Structural Analysis Program), with this program, it will be easier for writers to plan a building.The research carried out was to plan the structure of a six-story hotel building. This hotel building is the object of research planned by the author and was designed using the help of the SAP2000 program. Building design planning only includes planning beams and columns. In this plan the writer uses references such as regulations, PPPURG 1987, SNI 03-2847-2002, SNI - 1726 - 2002The results of the design of the hotel building structure used three variations that have the results of column K1 used size 45 cm x 45 cm, reinforcement base 12 D16 and stirrup reinforcement ?10-90, column K2 used size 35 cm x 35 cm, base reinforcement 8 D16 and stirrup reinforcement ?10-90, B1 beam used size 20 cm x 40 cm, support reinforcement 7 D14, field reinforcement 7 D14, waistline 2 D12, and support stirrup reinforcement ?10-80 and field stirrup ?10-170, beam B2 used size 15 cm x 20 cm, 75D14 support reinforcement, 5 D14 field reinforcement, 2 D12 waistline, and pedestal stirrup ulangan10-30 and field stirrup ?10-70